Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Kalimanggis Trans Logistics Tangerang Selatan - Farza Icmi Aula Rahman; Ichwan Nugroho (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. This study aims to analyze the influence of leadership style and work discipline on employee performance at PT Kalimanggis Trans Logistics, South Tangerang, with a sample of 71 employees. The research method used is quantitative with a descriptive approach. The data analysis techniques applied include the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, t-test, and F-test. The results indicate that leadership style has no significant effect on employee performance, as shown by the regression equation Y = 81.183 + 0.218X₁, with a correlation value of 0.205 and t-value < t-table (1.740 < 1.996), suggesting a weak relationship. Meanwhile, work discipline significantly affects employee performance, with the regression equation Y = 19.353 + 0.804X₂ and a correlation value of 0.811, indicating a strong relationship. Simultaneously, leadership style and work discipline significantly influence employee performance, as demonstrated by the regression equation Y = 37.419 + 0.440X₁ + 1.004X₂. The coefficient of determination (R²) is 0.770, indicating that 77.0% of employee performance variation is explained by the two variables. The F-test results show F-value > F-table (113.911 > 3.13) with a significance level of 0.000 < 0.05, confirming that leadership style and work discipline simultaneously have a significant effect on employee performance. Keywords: Leadership Style, Work Discipline, Employee Performance, Management.